Optimization Study on Carbonization of Palm Kernel Shell Using Response Surface Method - Alonge, O.I; Obayopo, S. O. (International Journal of Integrated Engineering, 2023)
The carbonization of Palm Kernel Shell (PKS) was carried out in a constant volume reactor and the optimization of the important factors (Temperature, Particle Size, and Residence time) that affect the quality of the biochar product was investigated using Response Surface Method (RSM-CCD). The characterization results before carbonization show that PKS is a potential biomass to be considered as an alternative for fossil fuel. Center Composite Design (CCD) was employed in the carbonization process to investigate the effect of process parameters on the quality of bio-char formed. The optimized conditions obtained for fixed carbon yield were temperature of 469.16oC, the particle size of mm, the residence time of 17.68 min, and these optimized conditions gave a fixed carbon of 79.65 % with a corresponding yield of 34.00 % while the temperature was observed to be the most influential factor. The optimized conditions were validated and the predicted results were in good agreement with the experimental results, as the relative error between the predicted and experimental values for the fixed carbon and corresponding percentage yield were -1.26 and 0.36 %, respectively. The study revealed the potential of PKS at different particle sizes considered, to be used as solid fuel.